FIXED POINT THEOREMS FOR FUNDAMENTALLY NONEXPANSIVE MAPPINGS IN CAT(K) SPACES - Nanjaras, B. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2016)
In this paper, we obtain fixed point theorems and $\triangle$-convergence theorems for fundamentally nonexpansive mappings on CAT(k) spaces with $k > 0$. Our results extend and improve some results of Salahifard et al. [3], and many others.